Pengaruh Serbuk Limbah Gypsum terhadap Nilai Daya Dukung dan Kuat Tekan pada Tanah Lempung Ekspansif di Lontar, Kecamatan Sambikerep, Surabaya - Novian Dhanny Chalik; Arik Triarsono; Anggi Rahmad Zulfikar; Irfan Prasetyo Loekito (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Expansive clay soil is soil that can expand and contract significantly in response to changes in soil moisture content. This study used an experimental method to stabilize expansive clay soil using a mixture of gypsum waste powder, which was tested using the Atterberg test, the Unconfined Compression Strength test, and the California Bearing Ratio test with mixture variations of 0%, 10%, 20%, and 30%. The results showed that the addition of gypsum waste powder could reduce the expansivity level of the soil from a very high level of 42% to a moderate level of 20%, increase the value in the Unconfined test at a maximum mixture of 10%, and increase the value in the CBR test at a maximum mixture of 30%. Based on the above description, this study aims to determine the extent of the effect of gypsum waste powder on expansive clay soil on the bearing capacity and compressive strength of expansive clay soil.